Relationships, learning, and development: A student perspective. Issue 137 (15th April 2013) - Bernstein‐Yamashiro, Beth; Noam, Gil G.
Abstract: In data derived from student interviews, students describe how they see teacher‐student relationships function for them in their experience of school, their personal development, and their academic success. These relationships are central to students' ability to feel connected at school and to their emerging identities. Students describe how certain teachers are able to reach out to them personally, enabling them to access curriculum and build a positive personal mentoring connection to an adult. Students also explain how being able to rely on relationships with their teachers helps them cope with the many emotional challenges they face as adolescents.